Correlation of Body Condition Score (SKT) to Limousin Cattle Reproduction Status in Purwantoro District, Wonogiri Regency - Ilham Fandi Ahmad; Engkus Ainul Yakin; Ludfia Windyasmara (Bantara Journal of Animal Science, 2021)
This study aims to determine the correlation between the Body Condition Score (SKT) on the reproductive status of limousine cattle in Purwantoro District, Wonogiri Regency. The research was conducted in 6 villages, namely Sumber Galih Village, Gondang Village, Joho Village, Kenteng Village, Purwantoro Village and Miricinde Village in Purwantoro District, Wonogiri Regency. ateri in the study were female limousine cows aged 2-4 years (productive age). Methods of data collection were carried out by conducting observations, direct interviews with breeders, and recording reproduction data from predetermined samples. Observations were made to assess the Body Condition Score (SKT). Interviews and reproduction data recording were carried out to assess reproduction views which included Service Per Conseption (S / C), Conception Rate (CR) scores or conception rates. The data analysis technique used is the t-test difference test (SPSS). The results showed that limousine cows with high HCS had low S / C values and high CR values, while limousine cows with low HCS had high S / C values and low CR values, so there was a correlation between HCS and reproductive status, namely the higher SKT gets better reproductive status and vice versa.Keywords: Conception rate, Limousine cow, Service per conseption, Body condition score